Renoprotective effects of GHRH agonist MR409 is associated with reduced oxidative stress and ferroptosis in diabetic mice - Liu, Yueyang; Fu, Rong; Tang, Qi; Zhang, Yaoxia; Cai, Ruiping; Liu, Limin; Jia, Hui; Gao, Junjia; Zhou, Ming-Sheng (Frontiers in Pharmacology, 2025)
MR409, a synthetic growth hormone-releasing hormone (GHRH) analogue, has demonstrated therapeutic potential in enhancing islet cell transplantation efficacy in diabetes mice and exerts beneficial effects on cardiovascular diseases. The present study investigated the renoprotective effects of MR409 on db/db and streptozotocin (STZ)-induced diabetic mice, focusing on its role in modulating oxidative stress and ferroptosis. db/db or STZ mice combined with high fat diet were used to establish the type 2 diabetic models. MR409 (15 μg/mouse/day) was subcutaneously administrated for 8 weeks. Treatment with MR409 significantly improved renal function, reduced the renal injury and fibrosis in both db/db and STZ-induced diabetic mice. MR409 increased the expression of renal GHRH receptor without affecting plasma level of the growth hormone. It attenuated oxidative stress, evidenced by decreased expressions of NADPH oxidase subunits p22phox, gp91phox, reduced dihydroethidium oxidative fluorescence intensity, and lowered renal expression of malondialdehyde and 4-hydroxynonenal in db/db mice. Meanwhile, MR409 inhibited ferroptosis, as indicated by upregulating the expressions of glutathione peroxidase 4, nuclear factor erythroid 2-related factor, ferritin heavy chain and downregulating transferrin receptor expression, alongside restoring renal glutathione level in db/db mice. Notably, MR409 activated the peroxisome proliferator-activated receptor γ and its downstream targeted gene Klotho in diabetic kidney. Collectively, the present study demonstrated that MR409 alleviates diabetic nephropathy, mitigates oxidative stress and ferroptosis, offering a novel therapeutic insight for diabetic nephropathy.